THE INFLUENCE OF HELPFUL BRAND ACTION ON RELATIONSHIP VALUE PERCEPTION THROUGH BEHAVIOURAL BRAND ENGAGEMENT IN GOJEK APPLICATION USERS IN SURABAYA - Harjanti, Dhyah; Peerera, Alvian Daniswara Agusta; Noerchoidah, Noerchoidah; Wijayadne, Devi Rahnjen (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Relationship value perception can be conceptualized as constructing a favorable relationship between a brand and its consumers. This is corroborated by the brand's beneficial actions, which facilitate consumer familiarity with the brand. This study aims to examine the influence of helpful brand action on relationship value perception through behavioural brand engagement in Go-Jek application users in Surabaya. A questionnaire was employed as the data collection technique, with a sample size of 350 respondents. This research utilizes a causal research design with quantitative methods. The data were analyzed using Smart PLS software. The findings indicate that helpful brand action affects behavioral brand engagement, that helpful brand action affects relationship value perception, and that behavioral brand engagement affects relationship value perception.